Ultra high performance liquid chromatography tandem mass spectrometry analysis of quorum-sensing molecules of Candida albicans - Gregus, Petr; Vlcková, Hana; Buchta, Vladimír; Kestranek, Jan; Krivcíková, Lucie; Nováková, Lucie (Journal of pharmaceutical and biomedical analysis, 2010)
Candida albicans is generally one of the most commonly isolated fungal pathogen from human body. It is a frequent cause of nosocomial infections, bloodstream infections, urinary infections and mucosal infections of oral cavity and vagina C. albicans can grow as hyphae, pseudohyphae, or budding yeast. Morphological conversion of a yeast form to pseudohyphal or hyphal one is often characterized by the change of commensal status to an invasive form. Farnesol and tyrosol can participate in these transformation processes as quorum sensing molecules together with some physical-chemical factors. A new analytical method for identification and quantification of biologically active substances farnesol and tyrosol using ultra high performance liquid chromatography (UHPLC) in connection with tandem mass spectrometry was developed. The analytes were separated on Acquity BEH C18 analytical column using binary mobile phase consisting of acetonitrile and formic acid 0.075% (75:25) at flow-rate 0.20 ml/min. SRM (selected reaction monitoring) mode was applied in order to ensure sufficient selectivity and sensitivity using the first most intensive transition as a quantitative (121>77 and 205>121) and second one for the confirmation purposes (121>93 and 205>109). The method was validated in terms of linearity (>0.9994), precision (0.5-3.8% RSD), accuracy (78.9-106.0%), LOD (limit of detection) and LOQ (limit of quantitation). The method can serve as an analytical tool for the detection and determination of quorum-sensing molecules in biological samples.
Keywords: Quorum Sensing; Chromatography, High Pressure Liquid; Limit of Detection; quorum sensing; limita detekce; Humans; Tandem Mass Spectrometry; fenethylalkohol; Female; lidé; farnesol; tandemová hmotnostní spektrometrie; hmotnostní spektrometrie s elektrosprejovou ionizací; Phenylethyl Alcohol; ženské pohlaví; Farnesol; Candida albicans; Spectrometry, Mass, Electrospray Ionization; kalibrace; vysokoúčinná kapalinová chromatografie; Calibration